Wearable Pressure Sensors for Pulse Wave Monitoring (Adv. Mater. 21/2022). Issue 21 (26th May 2022) - Meng, Keyu; Xiao, Xiao; Wei, Wenxin; Chen, Guorui; Nashalian, Ardo; Shen, Sophia; Xiao, Xiao; Chen, Jun
Abstract : Wearable Pressure Sensors In article number 2109357, Jun Chen and co‐workers introduce a kirigami‐inspired pressure sensor for wearable dynamic cardiovascular monitoring. Utilizing the vertical kirigami‐inspired structure and a simple fabrication process, the sensor provides an ascendant way for wearable electronics to overcome motion artifacts when monitoring human pulse signals, thus representing a solid advancement toward personalized cardiovascular monitoring in the era of the Internet of things.